With a dedication: "Seinem lieben Mitschuler Felix Kautsky zur frdl. Erinnerung, H. Willmann. ...... 5. IV. 06.", on the back
With a dedication: "Seinem lieben Mitschuler Felix Kautsky zur frdl. Erinnerung, H. Willmann. ...... 5. IV. 06.", on the back.